2015
DOI: 10.1128/jvi.03552-14
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleotide Exchange Factor Promotes Endoplasmic Reticulum-to-Cytosol Membrane Penetration of the Nonenveloped Virus Simian Virus 40

Abstract: The nonenveloped simian polyomavirus (PyV) simian virus 40 (SV40) hijacks the endoplasmic reticulum (ER) quality control machinery to penetrate the ER membrane and reach the cytosol, a critical infection step. During entry, SV40 traffics to the ER, where host-induced conformational changes render the virus hydrophobic. The hydrophobic virus binds and integrates into the ER lipid bilayer to initiate membrane penetration. However, prior to membrane transport, the hydrophobic SV40 recruits the ER-resident Hsp70 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…We next asked if the ERdj5-dependent reduction of SV40's disulfide bonds affects the ability of SV40 to bind to the ER-resident Hsp70 BiP (31,33). Affinity purification (AP) of S-tagged BiP (BiP-S) derived from infected cells transfected with either scrambled siRNA or ERdj5 siRNA 1 revealed that knockdown of ERdj5 decreased the SV40-BiP interaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next asked if the ERdj5-dependent reduction of SV40's disulfide bonds affects the ability of SV40 to bind to the ER-resident Hsp70 BiP (31,33). Affinity purification (AP) of S-tagged BiP (BiP-S) derived from infected cells transfected with either scrambled siRNA or ERdj5 siRNA 1 revealed that knockdown of ERdj5 decreased the SV40-BiP interaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory and others previously demonstrated that SV40 infection triggered selective ER membrane (e.g., BAP31) and soluble proteins to reorganize into these foci, where the virus also accumulates (12,25,31,52); these foci are thought to represent entry sites from where the viral particle penetrates the cytosol. If this is the case, we envision that impairment of SV40 entry into the cytosol should cause the virus to accumulate in the foci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most viruses therefore need cellular chaperones during their life cycle. Hsp70 proteins, as central components of the cellular chaperone network, are indeed frequently recruited by viruses (6,56,(73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%